2009
DOI: 10.1007/978-3-642-03613-2_24
|View full text |Cite
|
Sign up to set email alerts
|

Component-Trees and Multi-value Images: A Comparative Study

Abstract: In this article, we discuss the way to derive connected operators based on the component-tree concept and devoted to multi-value images. In order to do so, we first extend the grey-level definition of the component-tree to the multivalue case. Then, we compare some possible strategies for colour image processing based on component-trees in two application fields: colour image filtering and colour document binarisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…After a preliminary study of the relations between component-trees and multivalued images from a methodological point of view [1], a generalisation of component-trees to such images has been initiated in [2]. The present work develops this framework.…”
Section: Introductionmentioning
confidence: 99%
“…After a preliminary study of the relations between component-trees and multivalued images from a methodological point of view [1], a generalisation of component-trees to such images has been initiated in [2]. The present work develops this framework.…”
Section: Introductionmentioning
confidence: 99%
“…They allow users to chose properties of sections of the image that can be ignored, over-processed or filtered out. Connected filters have been used in various application, including image filtering and noise reduction [6], [7], [8], image simplification for compression [9], [10], video processing [10], [2], vessel enhancement filtering [11], [12], [13], and image analyzed microscopy [14]. Recent reviews can be found in [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Both are also referred to as component trees [17], [18], [8]. The aim of these trees is to encode a hierarchy of connected components at different levels to allow fast filtering or for analysis as a multi-scale representation of the image or volume under study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations